2012
DOI: 10.1016/j.jana.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Paper-Based Personal Health Record for HIV-Infected Persons

Abstract: A personal health record (PHR) contains information that a client believes is important to his/her health status; it can be either paper or Internet-based. The purposes of this action research were to determine the length of time an expert HIV nurse clinician needed to create a comprehensive PHR and determine how hard it is for the patient to understand different components of a PHR. The average respondent (N = 9) was older, female, completed high school, African American, diagnosed with AIDS, and taking HIV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As patients living with HIV are considered to be at higher risk of CVD, 30 the detection and management of both risk factors and manifest heart disease, along with a number of medications that HIV-infected patients take, have become a priority in the routine care of these patients. 31 - 33 …”
Section: Discussionmentioning
confidence: 99%
“…As patients living with HIV are considered to be at higher risk of CVD, 30 the detection and management of both risk factors and manifest heart disease, along with a number of medications that HIV-infected patients take, have become a priority in the routine care of these patients. 31 - 33 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have been carried out on a small sample size [24,25] and others on a very large one [26]. In this respect, researchers found that paper-based PHR studies encompassed a small sample size and electronic PHR studies had been conducted by employing a large sample size.…”
Section: Introductionmentioning
confidence: 99%